2019
DOI: 10.9734/afsj/2019/v10i230033
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Three Varieties of Mango

Abstract: Physical properties of three varieties of mango were studied at 13.75% and 8.74% moisture content levels. Some selected properties such as geometric mean, arithmetic mean, angle of repose, sphericity and crushing force were determined. The average tri-axial dimensions of the seeds gave 38.00 ± 6.8, 42.23 ± 4.12, 33.95 ± 6.91 as average major diameter; 35.60 ± 5.68, 39.18 ± 3.95, 31.44 ± 7.56 as average intermediate diameter and 24.76 ± 5.2, 28.42 ± 5.59, 23.08 ± 3.67 as average minor diameter for Kerosene, She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The geometric mean diameter represents the central tendency of the primary dimension and is normally used as parameter when designing fruit sorting machines [52,53]. Our result showed that the D g values were greater than reported by Osadare et al [54]. The arithmetic mean diameter (D a ) is also an important indicator in determining the quality attribute of a particular mango variety according to size and maturity stage [55].…”
Section: Physical Characteristics Of Mango Fruit Varietiesmentioning
confidence: 60%
“…The geometric mean diameter represents the central tendency of the primary dimension and is normally used as parameter when designing fruit sorting machines [52,53]. Our result showed that the D g values were greater than reported by Osadare et al [54]. The arithmetic mean diameter (D a ) is also an important indicator in determining the quality attribute of a particular mango variety according to size and maturity stage [55].…”
Section: Physical Characteristics Of Mango Fruit Varietiesmentioning
confidence: 60%